Perceived Organisational Support as a Mediator Between Green Organisational Culture and Organisational Commitment: Evidence From Manufacturing Firms in Peru - Cristian Villar; Ruben Guevara (SAGE Open)
As organisations increasingly focus on sustainability, green organisational culture has gained significant attention for its potential impact on various organisational outcomes. One such outcome, organisational commitment, plays a critical role in enhancing employee motivation, retention, and overall firm performance. Another important research variable that affects organisational commitment is perceived organisational support. This study examined the mediating role of perceived organisational support (POS) in the relationship between green organisational culture and organisational commitment in large and medium-sized manufacturing firms. Using a quantitative approach, the study used a non-experimental, cross-sectional design and employed partial least squares structural equation modelling (PLS-SEM) to analyse data from a random sample of 154 firms. Data were processed with SmartPLS 4 software. The results revealed that POS exerts a complementary mediation in the relationship between green organisational culture and organisational commitment. A positive association was found between green organisational culture and POS, which in turn positively influences organisational commitment. While the links between green organisational culture and organisational commitment have been explored, the role of POS as a mediator in that relationship has remained unexamined. This study addressed this gap by demonstrating how POS impacts the green organisational culture-organisational commitment relationship. These findings offer valuable insights for managers seeking to enhance organisational commitment. By promoting a green organisational culture and supporting POS, firms can improve employee commitment, contributing to organisational success. This study provides valuable empirical evidence within a new geographical and industrial context—namely, Peru’s manufacturing sector. Manufacturing firms play a crucial role in advancing global sustainability. The findings suggest that when companies integrate eco-friendly practices into their business models, they experience positive effects on organisational behaviour, which in turn enhances their competitiveness. Furthermore, in line with the organisational support theory, this is the first study that demonstrates the complementary mediating effect of POS on the green organisational culture-organisational commitment relationship.